Strategi Pengembangan Usaha Agroindustri Kopra di Negeri Mamala (Kecamatan Leihitu Kabupaten Maluku Tengah) - Okke Oktaviyanti Siregar; Leunard O. Kakisina; Maisie T. F. Tuhumury (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
It is necessary to know the strategy for developing the copra agroindustry in Mamala Village. Sampling was carried out using the purposive sampling method. The analysis tool us is the SWOT matrix. The results of the research show that the strategy used is to locate the copra industry close to the farmers' location so that there is cooperation between the industry and local farmers and it makes it easier for farmers to sell coconuts to the industry because the distance is quite close. The copra quality is good so it creates demand. there is always copra on the market, the availability of capital to buy coconut raw materials so that there is always coconut raw material to be produced into copra, the industry has a skilled workforce so that the potential for long-term copra products is quite good, even though the equipment technology for processing copra is still simple does not affect the long-term potential of copra products, having a small number of workers does not hinder the copra production process so that there is always a demand for copra in the market, the influence of uncertain market prices does not affect the good quality of copra, the existence of climate change on copra production is minimized because the availability of skilled workers in processing copra, having a small number of workers does not affect market access in selling copra products.